WEALTH DISPARITY AND ITS IMPACT ON SOCIAL MOBILITY - Ganapathi H B (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Wealth disparity, defined as the unequal distribution of assets and income among individuals and groups, has become an increasingly significant issue in modern societies. Its profound influence on social mobility—the ability of individuals or families to move up or down the socio-economic ladder—has raised concerns about the fairness and sustainability of economic systems. This paper explores the complex relationship between wealth inequality and social mobility, highlighting how the widening gap between the rich and the poor inhibits upward movement for disadvantaged populations. Rather than serving as a meritocratic platform where success is determined by talent and effort, modern economies often reflect entrenched privileges and barriers that correlate strongly with inherited wealth. The impact of wealth disparity manifests in multiple spheres of life, including education, healthcare, housing, and employment opportunities. Children from wealthier backgrounds benefit from high-quality schooling, well-connected social networks, and financial safety nets, giving them a significant advantage in achieving upward mobility. Conversely, those from low-income families often face underfunded schools, limited access to higher education, poor health outcomes, and geographic segregation, all of which contribute to a cycle of poverty that is difficult to escape. Moreover, the psychological effects of inequality—such as reduced ambition and a lack of perceived agency—further entrench social stratification. Through historical context and analysis of contemporary data, this study illustrates how wealth disparity has transformed from an economic issue into a social one, deeply affecting individual potential and societal cohesion. Addressing this imbalance requires systemic reforms in taxation, education, and social policy aimed at expanding opportunity and breaking down structural barriers. By doing so, societies can work toward restoring genuine social mobility and creating a more equitable and inclusive future. This paper calls for urgent attention to the link between economic inequality and diminished social mobility in order to promote long-term social progress.